Synthesis of novel 1-aryl-3-[2,3- or 4-(thieno[3,2-b]pyridin-7-ylthio)phenyl]ureas and evaluation as VEGFR2 tyrosine kinase inhibitors - Peixoto, Daniela (2013)
Vascular endothelial growth factor receptor 2 (VEGFR2) tyrosine kinase is involved in cancer and in angiogenesis. Herein, we report the synthesis of novel1-aryl-3-[2-, 3- or 4-{thieno[3,2-b ]pyridin-7-ylthio) phenyl]ureas as VEGFR2 inhibitors by promoting the regioselective attack of the thiol group of the 4-aminothiophenol in the chlorine nucleophilic displacement on 7-chlorothieno[3,2-b]pyridine 1, obtaining the aminated compounds Za- c. These were reacted with arylisocyanates to give the corresponding 1,3-diarylureas 3a-c, 4a-c and Sa-c (see scheme).